Christmas with his Cinderella - Gilmore, Jessica (Harlequin romance, 2021)
"With a string of luxury hotels to his name, brooding Baron Xander Montague needs help to freshen his public image. Reluctantly agreeing to adopt a rescue dog for Christmas, Xander isn't prepared for the whirlwind that is also part of the deal-- free-spirited dog nanny Elfie. But whisking her into his world, he discovers there's more to Elfie than he bargained for, and soon he can't imagine life without her-- or the dog--"--back cover.